Quantification of external and internal match loads in elite female team handball - Kniubaite, Audinga; Skarbalius, Antanas; Clemente, Filipe Manuel; Conte, Daniele (Biology of Sport, 2019)
To assess concurrently the external and internal match loads in elite female team handball players and to verify the differences in match loads between matches characterized by different durations. Eight elite female court handball players (mean±SD; age 23.0±2.1 years; stature 173.5±4.9 cm; body mass 67.8±6.8 kg) belonging to the same elite female handball team were investigated. Individualized internal and external match loads were monitored during seven 1st Division Lithuanian Women’s Handball League [Lietuvos Moteru Rankinio Lyga (LMRL)] matches and seven Women’s Baltic Handball League (WBHL) matches during the 2017/18 season. The LMRL and WBHL matches were characterized by different durations (two 30-min halves and two 20-min halves for LMRL and WBHL, respectively). The investigated external load measures were total player load (PL) and PL per minute (PL.min–1), while internal load measures were match load calculated from session rating of perceived exertion (S-RPE) and percentage of maximum heart rate (%HRmax). The main outcomes revealed a PL. min–1 of ~9 AU and ~84% of HRmax per match. Moreover, significantly higher total PL (p<0.001; ES (effect size) = Moderate) and match load calculated from S-RPE (p<0.05; ES= small to moderate) were found in LMRL compared to WBHL. Conversely, no statistically significant differences were found for PL.min–1 and %HRmax between the two leagues. The main results indicate that elite female handball matches require high physical and physiological demands. Additionally, a longer match time corresponded to dissimilar responses in external and internal match loads, suggesting that coaches should monitor match loads with different strategies.